Para uma "classificação genológica" das formas narrativas de ficção do período barroco. O contributo da novelas alegóricas em português dos séculos XVII e XVIII - Ramon, Micaela (2007)
Fictional narrative prose frotn baroque Portuguese authors raises a set of problems among which stands the question of genologic classification of texts produced at the time. In the frame of nar-rative literature of 17th and MP centuries, words as "romance" (romance), "novela" (novel) and "cont o" (tale) were used in a doubtful and as systematic way which had also, and above all, different meanings from those that they assume nowadays. Further, the word "novels" was then rejected because of its association with deft mare instead of docent. This paper will discuss the questions above starting from the analysis of texts an paratexts produced during the baroque period.